2019
DOI: 10.1109/access.2019.2901950
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Mild Depression Recognition Based on EEG-EM Synchronization Acquisition Network

Abstract: In this paper, we used electroencephalography (EEG)-eye movement (EM) synchronization acquisition network to simultaneously record both EEG and EM physiological signals of the mild depression and normal controls during free viewing. Then, we consider a multimodal feature fusion method that can best discriminate between mild depression and normal control subjects as a step toward achieving our longterm aim of developing an objective and effective multimodal system that assists doctors during diagnosis and monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Frontal (FP1, FP2, FPz) [68], [82], [100], [70], [ Not Mentioned [47], [48], [43] Most of these studies used EEG data from the individual modality and used a large number of electrodes. Out of 52 articles, 19 research articles have been found where authors have used 19 electrodes EEG device and the electrode positions for the 19-channel EEG are Fp1, Fp2, F3, F4, F7, F8, C3, C4, T3, T4, T5, T6, P3, P4, O1, O2, Fz, Cz, Pz.…”
Section: ) Signal Acquisition and Electrode Placementmentioning
confidence: 99%
See 4 more Smart Citations
“…Frontal (FP1, FP2, FPz) [68], [82], [100], [70], [ Not Mentioned [47], [48], [43] Most of these studies used EEG data from the individual modality and used a large number of electrodes. Out of 52 articles, 19 research articles have been found where authors have used 19 electrodes EEG device and the electrode positions for the 19-channel EEG are Fp1, Fp2, F3, F4, F7, F8, C3, C4, T3, T4, T5, T6, P3, P4, O1, O2, Fz, Cz, Pz.…”
Section: ) Signal Acquisition and Electrode Placementmentioning
confidence: 99%
“…However, as we have mentioned earlier, they used a certain stimulus where the authors used facial expression to picture block along with the neutral block of that person for a certain time. Zhu et al used an eye tracker along with the EEG Recording [43].…”
Section: ) Signal Acquisition and Electrode Placementmentioning
confidence: 99%
See 3 more Smart Citations